The Impact of Leadership Style in Local Government in the Development of Sustainable Micro Entrepreneurship - Isyak Meirobie; Agustinus Purna Irawan; Yugih Setyanto (Jurnal Komunikasi, 2022)
Micro entrepreneurship in several districts and municipalities has been growing rapidly. The progress of this micro entrepreneurship can be achieved because of the efforts of the micro entrepreneurship and the strength of the entrepreneurs. Entrepreneurship needs a sustainable system so that the micro business can be stronger and more developed. The development of the micro entrepreneurship also depends on the role and the partiality of its local government which is influenced by the leadership style of the local government itself. This study is conducted to identify the impact of the leadership style of local government, to develop the characteristic and style of leadership role in local government, and to comprehend the leadership communication within the set context. The research is done by applying qualitative method with descriptive analysis in which secondary and primary data are about the micro entrepreneurship in Belitung District, Indonesia. The results show that the style of leadership gives influence to the rapid growth of a system which create partiality, commitment, consistency that showed by the sustainable regulation and policy of the local government. The style of the leadership creates the face and the character of the micro entrepreneurship of the local district which surely also determines the development of the micro entrepreneurship itself.